1990
DOI: 10.1159/000266995
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoids in the Vitreous of Diabetic and Nondiabetic Human Eyes with Retinal Detachment

Abstract: We measured prostaglandin E2 (PGE2) and prostacyclin levels in the vitreous bodies of 5 eyes of patients with diabetic retinopathy complicated by rhegmatogenous retinal detachment (RRD) and compared them with the corresponding levels in 9 nondiabetic eyes with the same condition as well as with 10 control eyes of deceased patients with no known ocular pathology. We also studied the effect of surgical retinal reattachment on vitreal PGE2 and prostacyclin levels in 4 eyes. Vitrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Therefore, it is possible that these mechanisms may be involved in the pathophysiology of retinal vascular impairment in diabetic retinopathy. This notion is supported by the fact that the concentration of COX products in the vitreous is abnormal in diabetic animals [5] and in diabetic patients with proliferative retinopathy [6,7], and by the finding that diabetic patientshave abnormal endogenous NO synthesis, probably related to endothelial dysfunction [8,9]. It has previously been shown that interventions on the synthesis of NO and COX products interfere with diameter regulation of retinal arterioles during hypoxia in normal persons [10,11], but it remains unknown how these interventions may affect hypoxia-induced vasodilatation in diabetic patients, and especially whether the changes occur before the development of diabetic retinopathy to suggest a role in the early stages of the pathophysiology of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that these mechanisms may be involved in the pathophysiology of retinal vascular impairment in diabetic retinopathy. This notion is supported by the fact that the concentration of COX products in the vitreous is abnormal in diabetic animals [5] and in diabetic patients with proliferative retinopathy [6,7], and by the finding that diabetic patientshave abnormal endogenous NO synthesis, probably related to endothelial dysfunction [8,9]. It has previously been shown that interventions on the synthesis of NO and COX products interfere with diameter regulation of retinal arterioles during hypoxia in normal persons [10,11], but it remains unknown how these interventions may affect hypoxia-induced vasodilatation in diabetic patients, and especially whether the changes occur before the development of diabetic retinopathy to suggest a role in the early stages of the pathophysiology of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The special role of prostaglandin E 2 (PGE 2 ) in the induction of vascular inflamma-tion in neovascular retinal disorders [22][23][24] and its association with pathologic conditions such as damage due to laser irradiation [25,26], optic nerve injury [19] and retinal detachment [27] are well known. The major importance of prostaglandins in ocular diseases and injuries has been established [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Occlusive alteration of the vascular bed occurs, being mediated through platelet malfunction as a result of defects and aggregation of platelets [ 12,13]. Disturbances of hemostasis might be rebalanced by adding synthetic prostacyclin inhibiting the aggrega tion of platelets [2,3,14,15], Several studies correlated the plasma activity of prostaglan din and prostacyclin levels [16,17] with the development of diabetic retinopathies. Plas ma factors indicating prostacyclin-like activi ty in patients with diabetes mellitus were low er than in controls [ 18],…”
Section: Discussionmentioning
confidence: 99%